Stress concentration factor parametric formulae for concrete-filled rectangular hollow section K-joints with perfobond ribs. (September 2019) - Jiang, Lei; Liu, Yongjian; Fam, Amir; Liu, Jiang; Liu, Bin
Abstract: A new type of tubular joint made of rectangular hollow section (RHS) braces welded onto concrete-filled RHS (CFRHS) chords stiffened by longitudinally welding perfobond ribs to the inner faces has been studied earlier and demonstrated a better fatigue behaviour than a conventional empty RHS joint. In this paper, stress concentration factor (SCF) parametric design equations were developed for CFRHS K-joints with perfobond ribs through finite element (FE) analysis to fill a gap in current design guides for this type of K-joints. Three-dimensional FE models were developed using the ABAQUS software to simulate the hot spot stress distribution at the brace-chord intersection. FE results were successfully verified using experimental results of nine Y-joints from literature and one truss K-joint in this research. A comprehensive parametric study including 570 models was then carried out on CFRHS K-joints with perfobond ribs to examine the SCFs with five key dimensionless geometric parameters and three basic loading conditions involving axial loading in the chord and brace and bending in the chord. Consequently, a total of 36 SCF parametric equations were established using regression analysis. Subsequently, the number of formulae was reduced to six equations to predict the maximum SCFs for practical application. Highlights: Studying the Stress Concentration Factors (SCFs) for novel truss chord-brace welded K-joints Chord is a concrete-filled rectangular hollow section stiffened with perfobond ribs. FE modelling was developed against test results and then used in comprehensive study. Design equations developed using multiple regression analysis of the comprehensive database. Concrete filling and perfobond ribs stiffening reduces SCF by 41 to 69%.